2001
DOI: 10.1007/s00204-001-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of cadmium from infant diets in newborn rats

Abstract: Infants are exposed to higher levels of cadmium (Cd) from infant and follow-on formulas than from breast milk. We studied the bioavailability of 109CdCl2 from cows' milk formula, soy formula, wheat/oat/milk formula, wholemeal/milk formula and water in 11-day-old rat pups. The pups received a single oral dose of one diet labelled with 109Cd, 0.1 or 0.3 mg Cd/kg body weight. After 2 or 24 h or 4, 9 or 12 days the fractional retention of 109Cd in the whole body, in segments of rinsed small intestine and in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…The average oral absorption of Cd is low, up to 5% in adult humans (WHO 1992). Data for human infants are not available, but animal experiments suggest somewhat higher absorption in newborns (Kostial et al 1978;Nordberg et al 1978;Eklund et al 2001). Lower levels of Cd (not significantly) and higher levels of Se in both urine and faeces of pups supplemented with Se (both Se pre ?…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The average oral absorption of Cd is low, up to 5% in adult humans (WHO 1992). Data for human infants are not available, but animal experiments suggest somewhat higher absorption in newborns (Kostial et al 1978;Nordberg et al 1978;Eklund et al 2001). Lower levels of Cd (not significantly) and higher levels of Se in both urine and faeces of pups supplemented with Se (both Se pre ?…”
Section: Resultsmentioning
confidence: 92%
“…High and prolonged absorption of Cd, characteristic for newborn animals, is evident from the high level of Cd in the duodenum 24 h after the last Cd administration. Duodenum has been identified as the segment with the highest gastrointestinal Cd absorption in both adult (Sørensen et al 1993) and newborn animals (Eklund et al 2001). By tracking the retention of oral 109 Cd dose given in water or infant formula to 11-day-old rats, Eklund and co-workers also confirmed milk diet as a platform for higher Cd absorption and retention than water and cereal-or soy-based diets.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The bioavailability of cadmium from cow's milk formula, soy formula, wheat/oat/milk formula, whole meal/milk formula and water were compared in rat pups [256]. The pups received a single oral dose of one diet labelled with 109 Cd, 0.1 or 0.3 mg Cd/kg body weight.…”
Section: Phytic Acid Interactions With Toxic Trace Elements (Cd Pb)mentioning
confidence: 99%
“…Neonates are more sensitive to Cd toxicity than adults because of higher gastrointestinal absorption. 20 et al demonstrated that Cd transport in a model of neonatal intestinal cells correlated with expression of multidrug resistance-associated protein-1 but not with non-heme iron transporters such as DMT1. 22) Susceptibility of the intake and accumulation of Cd could vary depending on age.…”
Section: Discussionmentioning
confidence: 99%